2016
DOI: 10.1016/j.nucengdes.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark exercise for fluid flow simulations in a liquid metal fast reactor fuel assembly

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…This effort is described in Pacio et al (2017). There, it is shown that the wall resolved RANS model consisting of about 200 million cells can predict the pressure drop at similar accuracy as described earlier for Merzari et al (2016), Doolaard et al (2015), and Kennedy et al (2015). The main focus for validation was on temperatures and heat transport.…”
Section: Numerical Programmentioning
confidence: 74%
See 1 more Smart Citation
“…This effort is described in Pacio et al (2017). There, it is shown that the wall resolved RANS model consisting of about 200 million cells can predict the pressure drop at similar accuracy as described earlier for Merzari et al (2016), Doolaard et al (2015), and Kennedy et al (2015). The main focus for validation was on temperatures and heat transport.…”
Section: Numerical Programmentioning
confidence: 74%
“…The numerical benchmark reported by Merzari et al (2016), comprised 2 isotropic (realizable k-ε and SST k-ω) and 1 anisotropic (cubic k-ε) wall resolved RANS models. Mean velocities were predicted within 10% and in many cases within 5% with all applied turbulence models and a wall resolved mesh.…”
Section: Numerical Programmentioning
confidence: 99%
“…For some special applications, experimental data are utilized for a specific geometry and used to validate the numerical results [17,18]. For systems with lacking the experimental results, direct numerical simulations are used for generating test cases to verify the accuracy of a numerical implementation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the university of Texas performed a number of experiments in a 61-rods test section for code validation, as reported in Goth et al (2018), and for studying vortical structures that may occur in the flow, as described in and in . Computational Fluid Dynamics (CFD) studies have focused on modelling the flow around a single wrapped-wire pin (Shams et al, 2018;Fischer et al, 2007), and on simulating the entire bundle for validation purposes (Pointer et al, 2008;Merzari et al, 2016;Obabko et al, 2016;Brockmeyer et al, 2017). Depending on the position of the wire, the flow is found, unexpectedly, to bend against the direction of the wire.…”
Section: Introductionmentioning
confidence: 99%